Effect of Rapid Solidification Rates on Preparation of Ni-Pb Alloy Hollow Particles with Low Pb Content - Ka Gao; Yueyang Xu; Gaopeng Tang; Xiaoqin Guo; Rui Zhang (Journal of Spectroscopy)
Using Ni-5 wt.% Pb alloys with low Pb content as master alloys, the Ni-5 wt.% Pb alloy hollow particles were prepared by rapid solidification. Moreover, the alloy particles’ microstructure and formation mechanism were investigated. The results show that the particles’ microstructure consisted of Ni-rich and Pb phases. The Ni-rich phase was formed in the dendrite, and the Pb phase was distributed in the grain boundary or interdendrites. With the roller speeds increasing, the sizes of hollow particles and holes were decreased which were deviated from the particle center, while the hollow ratio, shear stress, and turbulence intensity of the hollow particles were increased. The formation of alloy hollow particles is attributed to interaction between the high-speed fluid and environment gas on the liquid/gas interface. The increase in roller speeds was conducive to the formation of Ni-Pb alloy hollow particles with low Pb content.